Bamboo Resources in Ethiopia: Their value chain and contribution to livelihoods - Mekonnen, Zenebe; Worku, Adefires; Yohannes, Temesgen; Alebachew, Mehari; Teketay, Demel -; Kassa, Habtemariam (Ethnobotany Research and Applications, 2014)
Ethiopia has an estimated one million hectares of natural bamboo forest, the largest in the African continent. Despite the versatile resource base and advanced bamboo utilization at a global scale, its great potential to enhance socio-economic and ecological development remains unrealized in Ethiopia. More importantly, recent observations in the country showed massive bamboo flowering followed by a death that urges management interventions. The objective of this study was to examine the socio-economic contribution of bamboo resources and typify their marketing value chain across major bamboo-growing and -marketing regions in Ethiopia, in order to promote its sustainable management. Structured questionnaires were administered to a total of 345 households to inspect the relative contribution of bamboo income to household economy. Participatory rural appraisal, key informant interviews, group discussions, market assessment, and field observations were made to understand the bamboo marketing system, actors involved, price trends, and factors affecting the bamboo value chain. Results show that crop and livestock production, forest management, and off-farm activities are major sources of income for respondent households. Fifty-three percent of the respondents reported bamboo income. Though it significantly varies across the study localities (p < 0.005), bamboo income contributed up to 11% of the annual cash income of the households, the lowest (3.4%) at Masha and the largest (38%) at Banja and Bahir Dar Zuria Districts. Positive and significant correlation was observed among cash incomes from bamboo, crop, petty trade, and other Non-Timber Forest Products (NTFPs). Producer farmers, village level traders, town and city wholesalers, small- and medium-scale bamboo processing and marketing firms, and town and city consumers are identified as major actors in the bamboo value chain. Fifty-five percent of the respondents indicated presence of poor horizontal and vertical linkage among actors. Access to market is difficult for a majority (88%) of the producers, and hence they sell bamboo culms and other product forms locally, mainly in roadside markets. Despite the inefficient value chains, 85% of the respondents indicated an increasing trend of demand for bamboo products. Market assessment for bamboo culms showed a price elasticity of demand, which is the change in quantity divided by change in price, up to 1.21 in 2008/2009 and 1.47 in 2009/2010. Nevertheless, bamboo utilization in Ethiopia is basically rudimentary, and bamboo product import exceeds export, in contrast to the resource base of the country. It is also noteworthy that the resource base is declining alarmingly in spite of the little interventions in place. An important policy and development lesson include enhancing further research for technology innovation, upgrading and integrating the bamboo value chain, and promoting sustainable management of the resource base.